2023
DOI: 10.1371/journal.pone.0283571
|View full text |Cite
|
Sign up to set email alerts
|

Mpox in Nigeria: Perceptions and knowledge of the disease among critical stakeholders—Global public health consequences

Abstract: Background The mpox (monkeypox) disease is a re-emerging viral zoonosis of international concern that is endemic in parts of Africa. The mpox virus (MPXV), which was hitherto largely limited to some Central and West African countries, was declared a public health emergency of international concern by the WHO on July 23, 2022 following the rapid spread of the virus to non-endemic countries. Globally, as of March 16, 2023, the WHO had reported 86,496 laboratory-confirmed cases of mpox and 111 deaths in 110 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 37 publications
0
24
2
Order By: Relevance
“…Similar results have been found in several studies on the use of radio and television as sources of information about the Mpox virus in different regions of the world. For example, Awoyomi OJ et al in Nigeria reported a prevalence of 12% in the use of radio as a source of information about the Mpox virus (20). In Brazil, Torres TS and his team reported that 13.7% of the population used radio for information about the virus, while 72.5% preferred television as a source of information (26).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar results have been found in several studies on the use of radio and television as sources of information about the Mpox virus in different regions of the world. For example, Awoyomi OJ et al in Nigeria reported a prevalence of 12% in the use of radio as a source of information about the Mpox virus (20). In Brazil, Torres TS and his team reported that 13.7% of the population used radio for information about the virus, while 72.5% preferred television as a source of information (26).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, access via the internet accounted for 61% (95% CI: 44-77%; 14002 participants; 5 studies; I 2 = 100%) (Figure S2) (26,28,30,31,33). As for radio, a level of 10% (95% CI: 07-13%; 8917 participants; 4 studies; I 2 = 93%) was observed (Figure S3) (20,(26)(27)(28), while television accounted for 24% (95% CI: 09-43%; 14896 participants; 8 studies; I 2 = 100%) (Figure S4) (26-28, 31,33,38,40,41). The combination of radio and television accounted for 45% (95% CI: 31-60%; 4207 participants; 7 studies; I 2 = 99%) (Figure S5) (21)(22)(23)29,34,36,37).…”
Section: Sources Of Information On Monkeypox Virusmentioning
confidence: 97%
See 3 more Smart Citations